Natronomicrosphaera hydrolytica, gen. nov., sp. nov., a first representative of the phylum Planctomycetota from soda lakes - Dimitry Y. Sorokin; Alexander Y. Merkel; Nicole J. Bale; Michel Koenen; Jaap S. Sinninghe Damsté; Laura Marturano; Enzo Messina; Violetta La Cono; Michail M. Yakimov (Systematic and Applied Microbiology, 2025)

Novel thermophilic hydrolytic bacterium Rarispira pelagica gen. nov., sp. nov., reclassification of Spirochaeta thermophila as Winmispira thermophila gen. nov., comb. nov., and proposal of Winmispiraceae fam. nov. and Winmispirales ord. nov. in the class Spirochaetia - Olga A. Podosokorskaya; Anastasiia I. Maltseva; Alexander G. Elcheninov; Andrei A. Novikov; Kseniya S. Zayulina; Alexander Y. Merkel (Systematic and Applied Microbiology, 2025)

A new type of submarine chimneys built of halite - C. Siebert; D. Ionescu; U. Mallast; S. Merchel; B. Merkel; P. Möller; S. Pavetich; T. Pohl; T. Rödiger; Y. Yechieli (Science of The Total Environment, 2024)

Corrigendum to “Natronospira bacteriovora sp. nov., and Natronospira elongata sp. nov., extremely salt-tolerant predatory proteolytic bacteria from soda lakes and proposal to classify the genus Natronospira into Natronospiraceae fam. nov., and Natronospirales ord. nov., within the class Gammaproteobacteria” [Syst. Appl. Microbiol. 47 (2024) 126519] - Dimitry Y. Sorokin; Alexander Y. Merkel; Tatyana V. Kolganova; Nicole J. Bale; Jaap S. Sinninghe Damsté (Systematic and Applied Microbiology, 2024)

Natronospira bacteriovora sp. nov., and Natronospira elongata sp. nov., extremely salt-tolerant predatory proteolytic bacteria from soda lakes and proposal to classify the genus Natronospira into Natronospiraceae fam. nov., and Natronospirales ord. nov., within the class Gammaproteobacteria - Dimitry Y. Sorokin; Alexander Y. Merkel; Tatyana V. Kolganova; Nicole J. Bale; Jaap S. Sinninghe Damsté (Systematic and Applied Microbiology, 2024)

Potential biosignatures in goethite deposits in Mavros Vrachos Quarry hypogene cave - G. Lazaridis; D. Bessas; M. Panou; B. Maróti; W. Crichton; V. Melfos; L. Papadopoulou; S. Gkelis; D.G. Merkel; A.I. Chumakov; P. Voudouris (CATENA, 2024)

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

Pythium insidiosum: insights into biofilm formation and antibiofilm activity of antifungal drugs - B. Pippi; E. S. Loreto; S. Merkel; A. R. Joaquim; M. E. Krummenauer; P. Reginatto; M. H. Vainstein; S. F. Andrade; A. M. Fuentefria; J. M. Santurio; R. A. Zanette (Brazilian Journal of Microbiology, 2023)

Desulfatitalea alkaliphila sp. nov., an alkalipilic sulfate- and arsenate- reducing bacterium isolated from a terrestrial mud volcano - M. A. Khomyakova; A. Yu. Merkel; V. S. Segliuk; A. I. Slobodkin (Extremophiles, 2023)

Role of drug delivery technologies in the success of COVID-19 vaccines: a perspective - Hagar I. Labouta; Robert Langer; Pieter R. Cullis; Olivia M. Merkel; Mark R. Prausnitz; Yasmine Gomaa; Sara S. Nogueira; Tushar Kumeria (Drug Delivery and Translational Research, 2022)

Natranaerofaba carboxydovora gen. nov., sp. nov., an extremely haloalkaliphilic CO ‐utilizing acetogen from a hypersaline soda lake representing a novel deep phylogenetic lineage in the class ‘ Natranaerobiia ’ - Dimitry Y. Sorokin; Martijn Diender; Alexander Y. Merkel; Michel Koenen; Nicole J. Bale; Martin Pabst; Jaap S. Sinninghe Damsté; Diana Z. Sousa (Environmental Microbiology, 2021)
Summary An anaerobic enrichment with CO from sediments of hypersaline soda lakes resulted in a methane‐forming binary culture, whereby CO was utilized by a bacterium and not the methanogenic partner. The bacterial isolate ANCO1 forms a deep‐branching phylogenetic lineage at the level of a new family within the class ‘ Natranaerobiia ’. It is an extreme haloalkaliphilic and moderate thermophilic acetogen utilizing CO, formate, pyruvate and lactate as electron donors and thiosulfate, nitrate (reduced to ammonia) and fumarate as electron acceptors. The genome of ANCO1 encodes a full Wood–Ljungdahl pathway allowing for CO oxidation and acetogenic conversion of pyruvate. A locus encoding Nap nitrate reductase/NrfA ammonifying nitrite reductase is also present. Thiosulfate respiration is encoded by a Phs/Psr‐like operon. The organism obviously relies on Na‐based bioenergetics, since the genome encodes for the Na + ‐Rnf complex, Na + ‐F1F0 ATPase and Na + ‐translocating decarboxylase. Glycine betaine serves as a compatible solute. ANCO1 has an unusual membrane polar lipid composition dominated by diethers, more common among archaea, probably a result of adaptation to multiple extremophilic conditions. Overall, ANCO1 represents a unique example of a triple extremophilic CO‐oxidizing anaerobe and is classified as a novel genus and species Natranaerofaba carboxydovora in a novel family Natranaerofabacea .

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

Microbial communities involved in the methane cycle in the near-bottom water layer and sediments of the meromictic subarctic Lake Svetloe - Vitaly V. Kadnikov; Alexander S. Savvichev; Andrey V. Mardanov; Alexey V. Beletsky; Alexander Y. Merkel; Nikolai V. Ravin; Nikolai V. Pimenov (Antonie van Leeuwenhoek, 2019)

Diltiazem Promotes Regenerative Axon Growth - Eric A. Huebner; Stéphane Budel; Zhaoxin Jiang; Takao Omura; Tammy Szu-Yu Ho; Lee Barrett; Janie S. Merkel; Luis M. Pereira; Nick A. Andrews; Xingxing Wang; Bhagat Singh; Kush Kapur; et al. (Molecular Neurobiology, 2019)

Acute hyperammonaemia induces a sustained decrease in vigilance, which is modulated by caffeine - E. P. Casula; P. S. Bisiacchi; M. Corrias; S. Schiff; C. Merkel; P. Amodio; S. Montagnese (Metabolic Brain Disease, 2015)

Wnt signaling induces gene expression of factors associated with bone destruction in lung and breast cancer - Rachelle W. Johnson; Alyssa R. Merkel; Jonathan M. Page; Nazanin S. Ruppender; Scott A. Guelcher; Julie A. Sterling (Clinical & Experimental Metastasis, 2014)

Structural Characteristics of Renal Glomerular System in ISIAH Rats under Conditions of Chronic Stress and Preventive Hypotensive Drug Therapy - E. E. Filyushina; M. D. Shmerling; V. A. Lazarev; I. I. Buzueva; A. L. Merkel; G. S. Yakobson (Bulletin of Experimental Biology and Medicine, 2011)

Non-invasive stimulation of the vibrissal pad improves recovery of whisking function after simultaneous lesion of the facial and infraorbital nerves in rats - H. Bendella; S. P. Pavlov; M. Grosheva; A. Irintchev; S. K. Angelova; D. Merkel; N. Sinis; K. Kaidoglou; E. Skouras; S. A. Dunlop; Doychin N. Angelov (Experimental Brain Research, 2011)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Effects of short-term treatment with diclofenac-colestyramine on renal function and urinary prostanoid excretion in patients with type-2 diabetes - K. Farker; U. Merkel; H. Schweer; J. Haerting; S. Madani; R. Eggers; U. Müller; H. Seyberth; A. Hoffmann (European Journal of Clinical Pharmacology, 2002)

Equation of state, elasticity, and shear strength of pyrite under high pressure - S. Merkel; A. P. Jephcoat; J. Shu; H.-K. Mao; P. Gillet; R. J. Hemley (Physics and Chemistry of Minerals, 2002)

Element and Sediment Accumulation Rates in the Florida Everglades - Robert S. Merkel; Rosemary Hickey-Vargas (Water, Air, & Soil Pollution, 2000)

Fungal disease resistance of Caribbean sea fan corals ( Gorgonia spp.) - K. Kim; C. D. Harvell; P. D. Kim; G. W. Smith; S. M. Merkel (Marine Biology, 2000)